Pengaruh Disiplin Kerja terhadap Kinerja Guru di SMA Negeri 5 Tana Toraja - Amazia Tofan Sampeuranag; Anwar Anwar; Uhud Darmawan Natsir; Romansyah Sahabuddin; Resky Amalia Hamka (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Amazia Tofan Sampeurang, 2024. The Influence of Work Discipline on Teacher Performance at SMA Negeri 5 Tana Toraja. Thesis of the Management Study Program, Faculty of Economics and Business, Universitas Negeri Makassar. Supervised by Anwar and Uhud Darmawan Natsir.This study aims to determine the influence of work discipline on teacher performance at SMA Negeri 5 Tana Toraja. This research uses a quantitative associative approach. Data were collected through questionnaires distributed to 56 teachers at SMA Negeri 5 Tana Toraja. Data analysis techniques used simple linear regression with the help of SPSS 24 software. The results of the study indicate that work discipline has a positive and significant influence on teacher performance. Indicators of work discipline such as punctuality, compliance with regulations, and commitment to carrying out tasks contribute to improving teacher performance. Additionally, a good work environment and support from the school principal also help foster high work discipline. This research demonstrates that improving work discipline can enhance teacher performance at SMA Negeri 5 Tana Toraja.